The Effect of Curcumin on Reactive Oxygen Species (ROS) Levels in the Hearts of Wistar Rats (Rattus norvegicus) as a Preeclampsia Model - Lina Zafirah Sukaji; Berliana Noviasih Pertiwi; Bambang Rahardjo; Husnul Khotimah (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Abstract Background: Reactive Oxygen Species (ROS) are reactive oxygen molecules that play a central role in the pathogenesis of preeclampsia through oxidative stress mechanisms. Elevated ROS levels trigger damage to membrane lipids, proteins, and DNA, as well as activate inflammatory pathways, leading to injury of target organs, including the heart. Curcumin, a polyphenolic compound derived from Curcuma longa, possesses antioxidant and anti-inflammatory properties with the potential to suppress ROS production and improve cellular function. Objective: To examine the relationship between ROS and curcumin by integrating experimental findings in a Wistar rat preeclampsia model with supporting literature. Methods: A literature review was conducted through searches in PubMed, Scopus, and Google Scholar using the keywords “Reactive Oxygen Species,” “Curcumin,” and “Preeclampsia.” Primary data were obtained from thesis research with a post-test only control group design, using L-NAME induction to generate a preeclampsia model and administering curcumin at a specific dose. ROS levels were measured using the spectrophotometry method. Results: The study showed that ROS levels in the preeclampsia group increased significantly compared to the control group (p < 0.05). Curcumin administration reduced ROS levels by 39.21% compared to the preeclampsia group, approaching control values. These findings are consistent with literature reports indicating that curcumin suppresses ROS through NADPH oxidase inhibition, increased antioxidant enzyme activity, and modulation of the NF-κB pathway. Conclusion: Curcumin significantly reduces ROS levels in the preeclampsia model and has the potential to serve as an adjunctive therapy in preventing complications mediated by oxidative stress. Keywords: Curcumin, Reactive Oxygen Species, Preeclampsia, Oxidative Stress, Antioxidant.